THE EFFECT OF THE PROJECT-BASED LEARNING MODEL ON THE CREATIVE THINKING ABILITY OF SCIENCE STUDENTS IN GRADE VIII SALAFIAH SYAFI'IYAH JUNIOR HIGH SCHOOL - Setiawan, Muhammad Muhyi; Sudarti, Sudarti; Handayani, Rif’ati Dina (Tesseract: International Journal of Geometry and Applied Mathematics, 2024)
This research employed an experimental method using the Project Based Learning (PJBL) instructional model to enhance students' creative thinking abilities in the subject of Natural Sciences (IPA) in the eighth grade of SMP Salafiah Syafi'iyah. The study involved two classes, one as the experimental group implementing PJBL learning model, and the other as the control group implementing conventional instructional model. Data were collected through pretests and post-tests measuring students' creative thinking abilities before and after the instruction. Data analysis involved descriptive and inferential statistics, including an independent t-test to compare the differences between the two groups. The descriptive analysis results indicated that the average post-test score in the experimental group (77.00) was slightly higher than that of the control group (72.00). However, this difference was not statistically significant. Furthermore, the normality analysis showed that both groups had a normal distribution of data. An independent t-test was conducted to examine the significant difference between the two groups. The test results revealed a significant difference between the experimental group and the control group in students' creative thinking abilities (p = 0.020). The mean difference between the two groups was 5.00, with a 95% confidence interval ranging from 0.81 to 9.19. Based on the findings of this study, it can be concluded that the implementation of the Project Based Learning (PJBL) instructional model has a positive influence on enhancing students' creative thinking abilities in the subject of Natural Sciences (IPA) in the eighth grade of SMP Salafiah Syafi'iyah.